Plasma Hemoglobin and Red Blood Cell Mass Levels as Dynamic Prognostic Markers for Progression and Survival in Pancreatic Neuroendocrine Tumors - Halperin, Reut; Ahron-Hananel, Genya; Badarna, Muhamad; Greidinger, Dahlia; Uri, Inbal; Percik, Ruth; Tirosh, Amit (Hormone and Metabolic Research, 2021)
There are scarce data on readily available markers enabling immediate risk stratification and personalized management in patients with advanced pancreatic neuroendocrine tumors. This study explores the association of red blood cells-related parameters as prognostic markers in patients harboring pancreatic neuroendocrine tumors. Retrospective analysis of a tertiary medical center database, acquiring data of patients with pancreatic neuroendocrine tumors including demographics, tumor-related parameters and consecutive imaging results, vital status at last follow-up, and red blood cells parameters at baseline, last follow-up, and dynamics (last/baseline ratio). Univariate and multivariable analyses were performed. Sixty-seven patients were identified (mean age at diagnosis of 63±11 years, 56.7% males). Patients with disease progression had lower hemoglobin, red blood cells mass values and hematocrit at the last evaluation (p<0.001 for all comparisons), with red blood cells mass level<3.9 m/μl and a 6% and 9% relative reduction in hemoglobin and hematocrit levels, respectively, associated with an increased risk for disease progression. Similarly, patients deceased during the study period had lower hemoglobin, red blood cells mass values and hematocrit (p<0.03 for all) than those alive, at last follow-up. Eleven percent reduction in hemoglobin level was noted indicating a higher mortality risk (p=0.04). Negative hemoglobin and hematocrit dynamics were independently associated with increased risk for disease progression (p=0.03 and 0.049, respectively). In conclusion, decrease in red blood cells mass, hemoglobin and/or hematocrit levels are all associated with poor prognosis in patients with pancreatic neuroendocrine tumors. We suggest utilizing these parameters as complementary follow-up prognostic markers to radiologic imaging in this patients population.
Keywords: prognosis; mortality; hematocrit; neuroendocrine tumor; pancreas; hemoglobin